Research and implementation of mobile DPI association algorithm with big data technology - Xiaosong LIU; Yi’an MA (Dianxin kexue)
In order to solve the problem of traffic usage caused by the increasing penetration rate of 4G in recent years,an algorithm that uses mobile DPI detailed bill and billing bill was proposed,and big data platform was adopted.The related processing technology implements the algorithm and shows the effect of the current network operation evaluation.